Mapping Internet and Social Media Use in Central Asia (International relations and international law Journal, 2023)
This article examines, updates and maps the use of the internet and social media in three Central Asian countries, using Kazakhstan, Kyrgyzstan and Uzbekistan as case studies. The aim is to generate systematic insights into the differences and similarities between the countries in the region in terms of the use and penetration of these media. The article highlights the uneven development of both media in the three countries and argues that the differences are related to the different socio-economic development and legal constraints in each country, with Kazakhstan leading the region in terms of internet and social media penetration and use, thus reversing the trend of the past when Kyrgyzstan was considered the most developed. The article concludes by stating that the internet and social media will continue to be important tools for communication and civic activism in the region, despite access and censorship problems, which, unlike in the past, have taken similar negative developments in the three countries in recent years. The study is based on secondary research.Key words: Internet, social media, mapping, Kazakhstan, Kyrgyzstan, Uzbekistan